A Systematic Review of Energy Efficiency Appliances Adoption in Developing Country - Aprilia, Hafiza; Prambudia, Yudha; Amani, Husni (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
This research examines the escalating energy demand, particularly driven by household electrical appliances in developing countries, highlighting a critical juncture for sustainable development. Through a systematic literature review, the study analyzes the complexity of energy-efficient appliance adoption with a comprehensive approach. Findings underscore the intricate interplay of economic, cultural, and technological factors shaping the adoption landscape, emphasizing the urgent need for transformative measures. Beyond identifying barriers, the research unveils best practices and success stories from developing countries, providing actionable insights. Technological innovations are explored as beacons of hope, offering tangible solutions to identified barriers. Government policy evaluation emphasizes the pivotal role of governance. The study concludes by underscoring the crucial importance of enhancing the adoption of energy-efficient household appliances in developing countries for sustainable development.